2011
DOI: 10.1152/ajpendo.00088.2010
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Nck1 attenuates hepatic ER stress signaling and improves glucose tolerance and insulin signaling in liver of obese mice

Abstract: Obesity has been shown to create stress in the endoplasmic reticulum (ER), and that initiates the activation of the unfolded protein response (UPR). This has been reported to cause insulin resistance in selective tissues through activation of the inositol-requiring enzyme 1α (IRE1α)-c-Jun NH2-terminal kinase (JNK) pathway, which results in the phosphorylation of the insulin receptor substrate-1 (IRS-1) at an inhibitory site and blocks insulin receptor signaling. In this study, we report that the Src homology d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 44 publications
4
48
0
1
Order By: Relevance
“…We and others implicated Nck in regulating the UPR through its interaction with the b-subunit of the eukaryotic initiation factor 2 (eIF2b) (8,10,11), Ser/Thr phosphatase PP1 (8,12), PERK (13,14), and IRE1a (7). We demonstrated that Nck1 is essential for sustained hepatic activation of the IRE1a-JNK pathway associated with impaired glucose homeostasis secondary to obesity in mice (15). We also have showed that Nck1 modulates PERK-dependent regulation of insulin biosynthesis and survival in pancreatic b-cells (13,14).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…We and others implicated Nck in regulating the UPR through its interaction with the b-subunit of the eukaryotic initiation factor 2 (eIF2b) (8,10,11), Ser/Thr phosphatase PP1 (8,12), PERK (13,14), and IRE1a (7). We demonstrated that Nck1 is essential for sustained hepatic activation of the IRE1a-JNK pathway associated with impaired glucose homeostasis secondary to obesity in mice (15). We also have showed that Nck1 modulates PERK-dependent regulation of insulin biosynthesis and survival in pancreatic b-cells (13,14).…”
mentioning
confidence: 88%
“…The antibodies used were as follows: Hsp90 (4877S) (44728G) from Invitrogen; Flag (3165) from Sigma; and Nck1 and panNck as previously described (10,15). The 3T3-L1 cell line from ATCC was cultured as recommended by the manufacturer.…”
Section: Antibodies and Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] Within this context, we identified a major role for Nck in regulating signaling from the ER through direct interaction with IRE1-a (Inositol-required enzyme 1-a) and PERK (double-stranded RNA-like ER kinase), [28][29][30][31][32] 2 fundamental components of the unfolded protein response (UPR), whose dysregulation has been implicated in the development of obesity. 33 It is noteworthy that obesity creates ER stress inducing sustained activation of the UPR in liver and adipose tissue, 34,35 potentially through increased production of reactive oxygen species 35 and impaired Ca 2C homeostasis.…”
Section: A Critical Role For Nck2 In Regulating Adipogenesismentioning
confidence: 99%
“…Nck module aussi la signalisation d'IRE1α (inositol requiring enzyme 1), autre protéine de la membrane du RE qui possède une activité kinase et une activité endonucléase activées dans les mêmes conditions de stress [10,32]. L'importance de Nck dans ce contexte s'est récemment accrue avec la découverte que les souris dont le gène Nck1 est inactivé sont protégées de la résistance à l'insuline résultant de l'activation anormale de la signalisation par IRE1α induite par l'obésité [26]. D'autre part, Nck joue aussi un rôle dans la réponse des cellules aux rayons UV, stress génomique qui provoque le transfert de Nck au noyau après son interaction avec SOCS7 (suppressor of cytokine signaling) [11].…”
Section: La Traduction Et La Réponse Au Stressunclassified